School Leadership and Innovative Educational Programs in Special Education School Units - Τάσσου Ευγενία; Ιορδανίδης Γεώργιος (Education Sciences, 2024)
In Greek reality, innovation is implemented through Interdisciplinary and European Educational Programs. The present study focuses on the leader and the way he influences the implementation and promotion of innovative educational programs in Special Education School Units. Methodologically, the utilization of mixed approaches was adopted. By random sampling, 242 participants from a total of 2,229 teachers working in Special Secondary Education Schools in the Greek territory completed the electronic questionnaire. With convenience sampling, 8 teachers were selected to conduct the interviews. Findings show that teachers perceive innovation in Special Education as the promotion of new concepts and identify it, primarily, with New Technologies. Multiple roles of innovative leader are clearly distinguished and emphasis is placed on the upgraded professional profile of Special Education director, to whom specific leadership practices are attributed for the introduction of innovative actions.